2020
DOI: 10.1007/s10708-020-10163-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effects of climate change on profit efficiency among small scale chili pepper marketers in Benue State, Nigeria

Abstract: In the determination of the level of efficiency of an enterprise, the role of climate change cannot be overemphasized. However, some scholars are of the view that climate change might not really affect the level of efficiency of an enterprise due to its indirect effect on the performance of an enterprise. Understanding the perception of marketers of agricultural produce about climate change in agribusiness is paramount to sustain small scale enterprises. This study sought to analyze the perceived effects of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Farmers argue that fluctuations in chili prices, including the high price of red chili, were caused by several factors, including weather, reduced numbers of farmers who grow red chili due to switching to other crops, disease and pests, and the significant import of red chili. The government needs to formulate several policies to overcome the fluctuations in red chili prices every year (Anwarudin et al, 2015;Djomo et al, 2021;Muñoz-Concha et al, 2020). First, the government needs to review the marketing aspect of growing red chili on new land in connection with the existing supply chain management.…”
Section: Figure 5 Price Of Red Chili In June 2019mentioning
confidence: 99%
“…Farmers argue that fluctuations in chili prices, including the high price of red chili, were caused by several factors, including weather, reduced numbers of farmers who grow red chili due to switching to other crops, disease and pests, and the significant import of red chili. The government needs to formulate several policies to overcome the fluctuations in red chili prices every year (Anwarudin et al, 2015;Djomo et al, 2021;Muñoz-Concha et al, 2020). First, the government needs to review the marketing aspect of growing red chili on new land in connection with the existing supply chain management.…”
Section: Figure 5 Price Of Red Chili In June 2019mentioning
confidence: 99%
“…The effect of weather shock is highlighted: farmers who faced yield loss due to weather shock operated at a significantly lower level of profit efficiency. Djomo et al (2021) also noted that excessive rainfall and drought can be decrease the profit efficiency of producers and marketers of chili pepper. Moreover, households with a non-farm income share also operated at a lower level of profit efficiency, indicating that the farmers had paid less attention to crop productivity than did the full-time farmers.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that environmental factors such as water pollution were serious problems and negatively affected profit efficiency. Djomo et al (2021) applied the Cobb-Douglas stochastic frontier model to determine the perceived effects of climate change on profit efficiency among small-scale chili pepper marketers in Benue State, Nigeria. Their findings revealed that rainfall variability, temperature variability and drought significantly affect their profit efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, climate change and diverse human activities have adversely affected the natural habitat that originally provided a home to animals such as the hyena around the environment inhabited by the Idoma people. According to Djomo et al (2021Djomo et al ( :1851, studies have shown that the average temperature in Nigeria has climbed to 31.83 Celsius in 2010 from 26.74 Celsius in the 18 th century. Generally, this is attributed to global warming, whose impact is noticeable all around the globe.…”
Section: Implications Of Odumu Performance On Environmental Sustainab...mentioning
confidence: 99%